Moral Consciousness as Philosophic Notion - Sliuzko, Valentyna; Plakhtii, Serhii (Pedagogical Discourse, 2014)
The problem of retrospective analysis of the key notion “Moral Consciousness» in philosophic sciences has been actualized. It is proved that the problem under research is topical, it is mentioned in the problem definition of the publication. The personals of the researchers of the sphere of humanitarian knowledge, in whose field of vision was scientific interest to the problem of moral consciousness, have been called. Analysis of the content of the key notions of the problem under research: “moral», “ethics», “moral consciousness» has been done in philosophic scientific researches. Within a framework of the article retrospective analysis of development of the world ethic thought in the sphere of morality of personality in ancient philosophy, Middle Age philosophy, renaissance, the Age of the Enlightenment, etc., has been done. It is generalized that folk pedagogics together with religion engendered folk deontology and theological ethics, which became the fundamentals of ethics, as a science about morality, moral consciousness, moral education. The conclusions generalize the idea that philosophy for a long time was the scientific source of study moral in human consciousness. Inside it ethics, pedagogics, psychology were formed. Development of these sciences is inseparable from the study of human consciousness in moral sphere. It was philosophy that determined the notion of morality as quite specific part of human consciousness in special forms of thinking using ethic notions and categories, and that has its range of problems.